Authentication of Andrographis paniculata in relation to Immunity (International Journal of Food and Nutritional Sciences, 2022)
Andrographis paniculata had multiple clinical applications in traditional systems of medicine. This research article deals with the estimation of immunity related compounds from Andrographis paniculata of aerial parts . Quantitative phytochemical analysis was carried out by UV visible spectrophotometer. Physico-chemical analysis was done to standardize the plant material so as to ensure the use of genuine material. The result of quantitative phytochemical studies confirmed that itcontains various secondary metabolites like total phenol, bound phenols, ortho dihydric phenols,flavonoids, tannins, anthocyanin, Leucoanthocyanin, chlorophyll, vitamin C, total carotenoids. UV visible spectrophotometer analysis confirmed the Andrographis paniculata contain different immunity booster compounds with varying amounts. This active constituent also exhibits antioxidant properties and also reduces viral infection therefore, it is used during Covid 19pandemic.